2021
DOI: 10.1021/acsami.1c11750
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Li1.3Al0.3Ti1.7(PO4)3 and LiNi0.6Co0.2Mn0.2O2 in Co-Sintered Composite Cathodes for Solid-State Batteries

Abstract: All solid-state batteries offer the possibility of increased safety at potentially higher energy densities compared to conventional lithium-ion batteries. In an all-ceramic oxide battery, the composite cathode consists of at least one ion-conducting solid electrolyte and an active material, which are typically densified by sintering. In this study, the reaction of the solid electrolyte Li1.3Al0.3Ti1.7(PO4)3 (LATP) and the active material LiNi0.6Co0.2Mn0.2O2 (NCM622) is investigated by cosintering at temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Literature showed that the elemental inter-diffusion in thermally unstable CAM/SSE combinations caused decompositions of CAM or SSE where the decomposed byproducts acted as insulating phases, strongly impeding the Li + transportation. [16,19,[21][22][23][24][25] Thus, thermal and chemical compatibilities of CAM/SSE at the processing temperature and (electro)chemical properties of the CAM/SSE interphase are the determining factors for the choice of CAM/SSE combinations.Phosphate-based NASICON-type Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 (LATP) is attractive to be employed as the SSE for ASSBs due to its competitive ionic conductivities and good chemical stability in ambient atmosphere. [26][27][28] LATP is considered to have better thermal stability with phospho-olivine LiMPO 4 (M: Fe, Mn, Co, Ni) cathodes because the oxygen atoms are tightly bound to P with the strong covalent bonds in both LATP and LiMPO 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Literature showed that the elemental inter-diffusion in thermally unstable CAM/SSE combinations caused decompositions of CAM or SSE where the decomposed byproducts acted as insulating phases, strongly impeding the Li + transportation. [16,19,[21][22][23][24][25] Thus, thermal and chemical compatibilities of CAM/SSE at the processing temperature and (electro)chemical properties of the CAM/SSE interphase are the determining factors for the choice of CAM/SSE combinations.Phosphate-based NASICON-type Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 (LATP) is attractive to be employed as the SSE for ASSBs due to its competitive ionic conductivities and good chemical stability in ambient atmosphere. [26][27][28] LATP is considered to have better thermal stability with phospho-olivine LiMPO 4 (M: Fe, Mn, Co, Ni) cathodes because the oxygen atoms are tightly bound to P with the strong covalent bonds in both LATP and LiMPO 4 .…”
mentioning
confidence: 99%
“…Literature showed that the elemental inter-diffusion in thermally unstable CAM/SSE combinations caused decompositions of CAM or SSE where the decomposed byproducts acted as insulating phases, strongly impeding the Li + transportation. [16,19,[21][22][23][24][25] Thus, thermal and chemical compatibilities of CAM/SSE at the processing temperature and (electro)chemical properties of the CAM/SSE interphase are the determining factors for the choice of CAM/SSE combinations.…”
mentioning
confidence: 99%
“…The threshold temperature is much lower than that predicted in a recent study of NMC-LATP thermo-mechanical compatibility (<550 °C) as the impact of the electrically conductive additive was not considered. 23 Under air, the transformations involve a cation redistribution in the NMC cathode material, leading to Mn-depletion at the surface. This cation migration is further accompanied by the loss of lithium and oxygen from the lattice as temperature increases and finally results in a phase transition from layered to spinel-type compounds and/or rocksalt oxides (depending on the temperature) as determined from XPS, EDX, and XRD.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Oxide-based ceramics as LATP require temperature-assisted densification techniques, with temperature ranges typically around 1000 °C and above . However, at such temperatures, the cathode components are not stable and can react to form resistive byproducts as well as to the structural degradation of the active material, which lead to the severe decay of the electrochemical performance. Ideally, the composite properties should remain unchanged, although chemical and structural modifications at the interfaces could be accepted, provided that Li-ion mobility is not obstructed. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation